Dreams and Stories in Hans Christian Andersen: Metanoia as a literary resource and community acceptance - Manso, Angelica Garcia (Aktualitet - Litteratur, kultur og medier, 2019)
This paper analyzes the motif of the "dream within the dream" or Metanoia as one of the most interesting structural components in the stories of Hans Christian Andersen. For example, the considerations about “The Shadow” (as well as other stories) reveal how, moreover, Metanoia has important repercussions on the aspect of "community acceptance" in the writer's work, without forgetting the role of Metanoia in the light of how stories are constructed through internal references and the duality between reality and dream.